What are the predictor variables of social well-being among the medical science students? - Nazila Javadi-Pashaki; Azar Darvishpour (Wolters Kluwer Medknow Publications, 2018)
Context: Individuals with social well-being can cope more successfully with major problems of social roles. Due to the social nature of human life, it cannot be ignored to pay attention the social aspect of health. Aims: The purpose of this study was to identify variables that predict the social well-being of medical students. Settings and Design: A descriptive-analytical study was conducted on 489 medical science students of Gilan Province, the North of Iran, during May to September 2016. Subjects and Methods: The samples were selected using quota sampling method. Research instrument was a questionnaire consisting of two parts: demographic section and Keyes social well-being questionnaire. Statistical Analysis Used: Data analysis was done using SPSS software version 19 and with descriptive and inferential statistics (t-test, ANOVA, and linear regression). Results: The results showed that majority of the students had average social well-being. Furthermore, a significant relationship between the academic degree (P = 0.009), major (P = 0.0001), the interest and field's satisfaction (P = 0.0001), and social well-being was seen. The results of linear regression model showed that four variables (academic degree, major, group membership, and the interest and field's satisfaction) were significantly associated with the social well-being (P < 0.05). Conclusions: The findings demonstrate that the different effects of the demographic factors on social well-being and the need for further consideration of these factors are obvious. Thus, health and education authorities are advised to pay attention students' academic degree, major, group membership, and the interest and field's satisfaction to upgrade and maintain the level of their social well-being.